Evaluation of four semi-permeable membranes in the osmotic technique for establishing soil-water retention curve (SWRC) of mansuli clay - Nurul Syafiqah, Mohd Azmi (2018)
Expansive clays are extensively used for various geotechnical and geoenvironmental applications in many countries especially as the backfilling and barrier materials in high-level radioactive nuclear waste disposal repositories. Detailed understanding of the behaviour of local expansive clay is extremely crucial to ensure the long term performance of the waste disposal repositories system in Malaysia. Suction and water content are the most important parameters that control the behaviour of expansive clay. Changes in water content due to changes in suction are commonly predicted by establishing the soil-water retention curves (SWRCs). In the laboratory, osmotic technique and vapour equilibrium technique were commonly used for controlling suction in the soil and to establish SWRCs. Several researchers revealed that osmotic technique has been widely used for applying lower suction less than 1 MPa but studies for higher suction are limited. The limitation of osmotic technique at higher suction is associated with the intrusion of polyethylene glycol (PEG) molecules into clay specimen due to failure of the semi-permeable membrane in restricting the passage of PEG molecules into clay specimen and affecting the precise determination of SWRCs. In this study, physical, chemical, mineralogical and microbiological properties of local expansive Mansuli clay were determined following the standard procedures. Besides that, drying and wetting SWRCs were established using osmotic, vapour equilibrium and chilled-mirror dew-point techniques to predict the behaviour of Mansuli clay at applied suction of 0.06 to 262.75 MPa. At higher applied suction, the osmotic tests were carried out using polyethersulfone (PES), thin film (TF) and polypiperazine-amide (PPA) semi-permeable membranes in order to prevent the intrusion of PEG molecules into clay specimen. The performance of semi-permeable membranes before and after osmotic tests was investigated using water flux test, permeability test and Atomic Force Microscopy (AFM). Based on the findings, Mansuli clay is classified as clay with very high plasticity (CV) due to high specific surface area and cation exchange capacity. Mansuli clay contains vermiculite as the main mineral (36.8%) and this local clay is magnesium-rich type vermiculite with weighted average valency of about two. In total, five species of microbes were found within Mansuli clay. The PEG intrusion occurred at higher applied suction (i.e. suctions between 3 and 10 MPa) in osmotic test using cellulose acetate (CA) membrane and the water contents obtained from osmotic test were found to be lower than water contents obtained from vapour equilibrium test. Two of the fungus identified namely Penicillium funiculosum and Hypocrea aureoviridis were believed to be accountable for degradation of CA membrane in osmotic test. At the end of the research, it was found that PES membrane was able to minimise the effect of PEG intrusion into clay specimen at higher suction and the water contents obtained from osmotic test were found to be in good agreement with that obtained from vapour equilibrium test. Smooth and precise drying and wetting SWRCs of Mansuli clay were established using PES membrane. Thus, this study overcomes the limitation of osmotic technique at higher suction and a better prediction of engineering behaviour of local clay can be provided. This study also provides information for possible use of Mansuli clay as barrier material for the development of Malaysia nuclear waste repositories.